2021
DOI: 10.1002/cncr.33426
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and prostate cancer screening, incidence, and mortality: Results from the Henry Ford Exercise Testing (FIT) Project

Abstract: Background The relation between cardiorespiratory fitness (CRF) and prostate cancer is not well established. The objective of this study was to determine whether CRF is associated with prostate cancer screening, incidence, or mortality. Methods The Henry Ford Exercise Testing Project is a retrospective cohort study of men aged 40 to 70 years without cancer who underwent physician‐referred exercise stress testing from 1995 to 2009. CRF was quantified in metabolic equivalents of task (METs) (<6 [reference], 6‐9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…Another perhaps surprising finding was that a healthy lifestyle was associated with an increased risk for prostate cancer (HR: 1.04 per 1-point increment in HLI; 95% CI: 1.01-1.06) and melanoma (HR: 1.09; 95% CI: 1.04-1.15), the former perhaps due to screening practices, as has been suggested previously ( 10 ), and the latter perhaps due to ultraviolet exposure from outdoor physical activity. Although this certainly does not negate the overwhelming benefits of a healthy lifestyle overall, this finding does point out that there is significant heterogeneity between lifestyle factors and certain cancers.…”
supporting
confidence: 59%
“…Another perhaps surprising finding was that a healthy lifestyle was associated with an increased risk for prostate cancer (HR: 1.04 per 1-point increment in HLI; 95% CI: 1.01-1.06) and melanoma (HR: 1.09; 95% CI: 1.04-1.15), the former perhaps due to screening practices, as has been suggested previously ( 10 ), and the latter perhaps due to ultraviolet exposure from outdoor physical activity. Although this certainly does not negate the overwhelming benefits of a healthy lifestyle overall, this finding does point out that there is significant heterogeneity between lifestyle factors and certain cancers.…”
supporting
confidence: 59%
“…24 The influence of potentially higher prostate cancer screening rates in those with higher CRF has been put forward as an explanation for the counterintuitive association between CRF and prostate cancer incidence found in this study and others. 8 Reiter-Brennan et al 11 reported that men with high CRF had a 28% higher risk of completing prostate cancer screening in comparison with men with low CRF. It is important to also consider that prostate cancer is the most heritable cancer, with a reported 58% of the variability in risk attributable to inherited risk factors, 25 meaning that lifestyle factors may be less likely to influence prostate cancer incidence rates than other cancers prone to lifestyle-related cancer-causing agents.…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, analysis of the association between CRF and both cancer incidence and mortality in the same study, reported by cancer type, and conducted in large population samples are lacking in existing studies. [8][9][10][11] Moreover, previous studies have typically only examined main effects, thereby ignoring important interaction analyses of, for example, when in adulthood associations between CRF and cancer outcomes are particularly strong or weak. As increasing age is one of the strongest risk factors for several cancer forms 12 and CRF levels tend to decrease with older age, 13 the associations between CRF and cancer incidence and mortality risk may vary depending on when in life CRF is assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancing age, black race, and family history are well-established risk factors for prostate cancer ( 3 ). Meanwhile, more lifestyle and dietary risk factors that might increase the risk of prostate cancer have been consecutively put forward, like obesity ( 4 ), fitness ( 5 ), diabetes mellitus ( 6 ), dietary patterns ( 7 ), and supplementation with vitamin E ( 8 ). Moreover, human development index (HDI), a summary measure of average achievement in key dimensions of human development for each country including life expectancy at birth, education index, and gross national income per capita ( 9 ), has demonstrated an impact on the incidence and mortality of prostate cancer ( 1 3 ).…”
Section: Introductionmentioning
confidence: 99%